Fabrication of flexible multilayer transparent electrode based on silver nanowire, graphene oxide, and poly(3,4-ethylenedioxythiophene): polystyrene sulfonate - Nguyen, Thi Thu Hien; Nguyen, Minh Hoang; Khong, Minh Triet; Nguyen, Thi Kim Dung; Doan, Tien Dat; Hac Thi, Nhung; Oanh, Ho Thi; Tuyen, Nguyen Duc; Phan, Dinh Long; Nguyen, Tuyen Van; Hoang, Mai Ha (Vietnam Journal of Science and Technology, 2022)
High-performance flexible multilayer transparent conducting electrodes (TCE) based on silver nanowires (AgNWs), graphene oxide (GO), and poly(3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) materials on the flexible polyethylene terephthalate (PET) substrate were successfully fabricated by spin-coating technique. The multilayer electrodes were fabricated using different combinations of AgNWs, GO, and PEDOT:PSS materials. The morphological, physical properties, surface roughness, and durability of the fabricated electrodes were investigated. The results indicated that the five-layer structured electrode of PEDOT:PSS/GO/AgNW/GO/PEDOT:PSS possesses the best performance with a sheet resistance of 23 Ω/sq, transmittance of 85 %, and the figure of merit (FoM) value of 8.6, which is equivalent to the commercial ITO electrode. Besides, the five-layer structured electrode possessed a surface roughness of only 8 nm. The PEDOT:PSS/GO/AgNW/GO/PEDOT:PSS electrode also exhibited high durability after being exposed to the environment for 30 days. Owing to the combination of AgNWs, GO, and PEDOT: PSS materials, the five-layer electrode of PEDOT:PSS/GO/AgNW/GO/PEDOT:PSS improved the inherent disadvantages of AgNWs electrodes. In addition, the electrode possessed good conductivity, high stability, low cost, and simplicity. The electrode can be used as a promising electrode in optoelectronic devices.